2020
DOI: 10.1002/cam4.3293
|View full text |Cite
|
Sign up to set email alerts
|

DNA aneuploidy with image cytometry for detecting dysplasia and carcinoma in oral potentially malignant disorders: A prospective diagnostic study

Abstract: Background Current evidence on diagnostic value of aneuploidy with DNA image cytometry (ICM) using brushings for oral potentially malignant disorders (OPMD) is limited by sample size and inconsistent classification criteria of aneuploidy. This study aimed to explore the optimal cut‐off values of DNA content and evaluate the diagnostic accuracy of DNA‐ICM for detecting dysplasia and/or carcinoma in OPMD. Materials and Methods A total of 401 consecutive patients with OPMD were enrolled in this prospective diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Several groups have confirmed the value of DNA ploidy as a predictor of malignant transformation (Bradley et al, 2010;Bremmer et al, 2011;Siebers et al, 2013;Sperandio et al, 2013;Torres-Rendon et al, 2009;Zaini et al, 2018). Abnormal DNA ploidy correlates with the presence and severity of dysplasia (Donadini et al, 2010;Grässel-Pietrusky et al, 1982;Pentenero et al, 2009;Saito et al, ,1995Saito et al, , , 1998van Zyl et al, 2012), is more frequently found in higher grades of dysplasia (Li et al, 2020;Sperandio et al, 2013;van Zyl et al, 2012) and in lesions considered high-risk clinically (Xiao et al, 2015;van Zyl et al, 2012). Correlation with dysplasia is not necessarily an advantage since the predictive value of dysplasia is reported to be extremely variable, but DNA ploidy is able to detect changes in OPMD that have minimal or no dysplasia (Sperandio et al, 2013;Zaini et al, 2018), as can flow cytometry (Pentenero et al, 2012).…”
Section: Dna Aneuploidymentioning
confidence: 92%
See 3 more Smart Citations
“…Several groups have confirmed the value of DNA ploidy as a predictor of malignant transformation (Bradley et al, 2010;Bremmer et al, 2011;Siebers et al, 2013;Sperandio et al, 2013;Torres-Rendon et al, 2009;Zaini et al, 2018). Abnormal DNA ploidy correlates with the presence and severity of dysplasia (Donadini et al, 2010;Grässel-Pietrusky et al, 1982;Pentenero et al, 2009;Saito et al, ,1995Saito et al, , , 1998van Zyl et al, 2012), is more frequently found in higher grades of dysplasia (Li et al, 2020;Sperandio et al, 2013;van Zyl et al, 2012) and in lesions considered high-risk clinically (Xiao et al, 2015;van Zyl et al, 2012). Correlation with dysplasia is not necessarily an advantage since the predictive value of dysplasia is reported to be extremely variable, but DNA ploidy is able to detect changes in OPMD that have minimal or no dysplasia (Sperandio et al, 2013;Zaini et al, 2018), as can flow cytometry (Pentenero et al, 2012).…”
Section: Dna Aneuploidymentioning
confidence: 92%
“…Very small amounts of tissue are required for analysis. Both flow cytometry and image cytometry can be applied to scrapings of mucosa, endoscopic forceps biopsy, brush biopsy or other cytological specimens (Cowpe et al, 1985;Dineshkumar et al, 2019;Kammerer et al, 2013;Pektas et al, 2006;Remmerbach et al, 2001Remmerbach et al, , 2003Velleuer et al, 2020) and results match those on incisional biopsy (Li et al, 2020;Maraki et al, 2004) and correlate with clinical risk F I G U R E 1 Typical DNA ploidy histograms obtained by image-based cytometry. Y-axis total nuclei analysed and X-axis optical density in Feulgen stain is directly proportional to DNA content, calibrated as c value (2c = diploid).…”
Section: Dna Aneuploidymentioning
confidence: 99%
See 2 more Smart Citations
“…The following supporting information can be downloaded at: , Table S1: Summary characteristics of included studies [ 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 <...…”
mentioning
confidence: 99%